Optimalisasi Produktivitas Alat Gali Muat Rocker Shovel Dan Alat Angkut Angkut Grandby Mine Car Untuk Menunjang Tercapainya Produksi Bijih Emas (Primer) Pada Kegiatan Penambangan Tambang Bawah Tanah PT. Dempo Maju Cemerlang. - Wiza Esti Ningrum; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2023)
PT. Dempo Maju Cemerlang is a former Dutch colonial mine that operates as a gold mining company in Nagari Tambang, Pesisir Selatan Regency, using the Shrinkage Stope method, namely an overhand mining system to create a body with a slope of between 50o-90o. This research aims to analyze the compatibility value between the rocker shovel digging and loading equipment and the Grandby Mine car transportation equipment at PT. Dempo Maju Cemerlang and created simulations to improve working time and standby time for loading and digging equipment and transportation equipment. This research uses a quantitative type of research. The results of calculations using match factor, obtained a value of MF<1, where the loading equipment will wait while the transportation equipment is working fully or not in harmony. After improvements were made to working time and standby time, the results showed that the work effectiveness of the rocker shovel loading equipment was 38.93% and the effectiveness of the grandby transportation equipment at level 6 was 40%. Meanwhile, the effectiveness of Grandby transportation equipment at level 7 is 39.55%. This increase affects productivity, where the productivity of the rocker shovel conveyance is 2384,42 tonnes/month, the productivity of the Grandby conveyance at level 6 is 2276,73 tonnes/month, and the productivity of the Grandby conveyance at level 7 is 2243,16 tonnes/month.Keywords: Shrinkage Stope, rocker shovel, Grandby, match factor, productivity